Experimental investigation of thermal effects on dynamic behavior of granite. (October 2017) - Fan, L.F.; Wu, Z.J.; Wan, Z.; Gao, J.W.
Highlights: Temperature significantly influence the dynamic behavior of granite. Density variation (within 5%) can be ignored during thermal treatment. Wave velocity and Young's modulus decreases as temperature increases monotonously. Energy absorption ability varies as temperature increases with its maximum at 400 °C. Abstract: A systemic understanding of the thermal effects on the dynamic behavior of granite is significant to thermal engineering applications such as waste disposal engineering and underground coal gasification. In the present study, scanning electron microscope (SEM) tests were carried out to evaluate the thermal effects on the geophysical properties of granite. The results show that the density decreases slightly as the temperature increases from 25 °C to 400 °C but that it decreases sharply as the temperature increases further to our maximum tested temperature of 800 °C. The defect rate increases slightly as temperature increases from 25 °C to 400 °C and then increases sharply as the temperature further increases to 800 °C. Next, ultrasonic wave tests were performed to evaluate the thermal effects on the wave velocity and P-wave modulus. The results show that both the wave velocity and P-wave modulus decrease sharply and linearly below the temperature of 400 °C, before deceasing nonlinearly as the temperature increases to 800 °C. Finally, split Hopkinson pressure bar (SHPB) tests were adopted to investigate the thermal and loading rate coupling effects. The results show that the dynamic strength decreases linearly as temperature increases but increases as the impact pressure increases. However, the dynamic energy absorption capacity increases below 400 °C but then decreases as the temperature increases to 800 °C. The thermal effects on energy absorption capacity are more obvious for granite under a smaller impact pressure.